BIOCHEMICAL SCREENING OF MARINE MICROMONOSPORA MARINA KPMS1 (MH036351) AND ITS ANTIBACTERIAL ACTIVITY AGAINST MULTIDRUG RESISTANT BACTERIA - M, MOHAMED MAHROOP RAJA; A, RAJA; N, REEHANA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present investigation aimed at the screening of pharmaceutically potential antimicrobial metabolite isolated from marine Micromonospora sp. to combat the multidrug‑resistant bacteria. Materials and Methods: The Marine sediments were randomly collected for the isolation of Micromonospora sp., from Gulf of Mannar, East Coastal Region, located at Kayalpatnam, Tuticorin district, Tamil Nadu, India. The Micromonospora sp. was cultivated by serial dilution and crowed plating method on actinomycetes isolation agar. The isolated colonies were identified by morphological, cultural, and biochemical methods. The antibacterial study of Micromonospora sp. was performed on Mueller‑Hinton agar medium against multidrug‑resistant bacteria isolated from urinary tract infection. The antibacterial compound was separated and characterized by Fourier‑transform infrared (FT‑IR) and nuclear magnetic resonance (NMR) spectrum. Results: Based on the morphological, cultural, and biochemical studies, the isolated colonies were found to be the genera of Micromonospora. Among Micromonospora genera, Micromonospora marina KPMS1 strain showed potent antibacterial activity against multidrug‑resistant Escherichia coli, Pseudomonas aeruginosa, and Enterococcus faecalis. The FT‑IR and NMR studies showed the structural elucidation of active compounds derived from M. marina KPMS1. The 16S rRNA sequences of M. marina KPMS1 (MH036351) strain were blasted and deposited in the GenBank of National Center for Biotechnology Information. Conclusion: The results of the study were concluded that microbial compounds are the promising sources of nearly all of the antibiotics produced by marine Micromonospora sp. The detection of new biological compounds was considered to represent a novel species of the genus Micromonospora which have been used for clinical treatment against multidrug‑resistant bacteria and were pharmaceutically important.